pengaruh kombinasi ekstrak benalu teh dan mangga terhadap profil histopatologi tikus hipertensi (DOCA-SALT) - Oktaviana, Nimas Ajeng; Abdoes Sjakoer, Nour Athiroh; Mubarakati, Nurul Jadid (Universitas Islam Negeri Mataram, 2021)
The purpose of this study was to analyze the brain histopathological profile in hypertensive rats (DOCA-Salt) treated to Tea and Mango extract combination (Mistletoe). Samples were obtained using a true experimental design completely randomized on 25 rats with three treatments (TI, TII, TIII), negative control, and positive control with replication five times. Ratio of extract for treatment was 3 : 1 made up 50 mg/kg BW, 100 mg/kg BW, 200 mg/kg BW. Data analysis using one-way analysis of variance (ANOVA) with the JAMOVI application. The study results obtained Mistletoe (Tea and Mango) extract combination in hypertensive rats (DOCA-Salt) can significantly reduce the necrosis of brain cells in the white matter area. The combination of Mistletoe extract can reduce the number of brain cell necrosis in hypertensive rats optimally obtained at a dose of 50 mg/kg BW